Plasticity of Lateral Root Branching in Maize - Yu, Peng; Hochholdinger, Frank; Li, Chunjian (Frontiers in Plant Science, 2019)
Extensively branched root systems can efficiently capture soil resources by increasing their absorbing surface in soil. Lateral roots are all roots that are formed postembryonically from pericycle cells of axial other roots and main root are thus thinner than these main roots. As a consequence, lateral roots provide a higher surface to volume ratio and are better equipped for an effective uptake of water and nutrients. In this review, we will mainly focus on the spatial distribution of soil-grown lateral roots of maize and their developmental plasticity in response to water and nutrient availability. Recent discoveries on root responses to water and nutrients contribute to the understanding of how plant root system adapt to environmental changes and efficiently capture soil resources.